2016
DOI: 10.1093/nar/gkw1210
|View full text |Cite
|
Sign up to set email alerts
|

RMI1 and TOP3α limit meiotic CO formation through their C-terminal domains

Abstract: At meiosis, hundreds of programmed DNA double-strand breaks (DSBs) form and are repaired by homologous recombination. From this large number of DSBs, only a subset yields crossovers (COs), with a minimum of one CO per chromosome pair. All DSBs must be repaired and every recombination intermediate must be resolved to avoid subsequent entanglement and chromosome breakage. The conserved BLM-TOP3α-RMI1 (BTR) complex acts on early and late meiotic recombination intermediates to both limit CO outcome and promote chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 48 publications
5
67
0
Order By: Relevance
“…Unexpectedly, these studies revealed that Rmi1 and Top3 act independently of Sgs1 to disentangle chromosomes in late meiotic prophase, allowing for proper chromosomal segregation [12,40]. Similar BLM-independent roles for RMI1 and TOP3α have been described in Arabidopsis [20, 4143] and C. elegans [44], but it is likely that functions described below for BLM orthologs also require these interacting proteins.…”
Section: S Cerevisiae Sgs1: the Pioneering Meiotic Pathway Regulatormentioning
confidence: 86%
“…Unexpectedly, these studies revealed that Rmi1 and Top3 act independently of Sgs1 to disentangle chromosomes in late meiotic prophase, allowing for proper chromosomal segregation [12,40]. Similar BLM-independent roles for RMI1 and TOP3α have been described in Arabidopsis [20, 4143] and C. elegans [44], but it is likely that functions described below for BLM orthologs also require these interacting proteins.…”
Section: S Cerevisiae Sgs1: the Pioneering Meiotic Pathway Regulatormentioning
confidence: 86%
“…Increasing recombination is thus a desired trait in plant breeding 8,9 . Forward screen approaches have identified thee pathways that limit recombination in Arabidopsis thaliana , relying respectively on the activity of (i) FANCM helicase and its cofactors 1,10 , (ii) the BLM/Sgs1 helicase homologues RECQ4A and RECQ4B and the associated proteins TOP3α and RMI1 2,11 ;(iii) the FIGL1 AAA-ATPase 3 . RECQ4A and RECQ4B are duplicated genes that redundantly limit meiotic crossovers in Arabidopsis , and will be herein designated as RECQ4, for simplicity.…”
Section: Figurementioning
confidence: 99%
“…However, only ∼10 crossovers typically form throughout the genome 1821 , indicating that anti-crossover pathways prevent maturation of the majority of initiation events into crossovers. Indeed, genetic analysis has identified at least three distinct anti-crossover pathways in Arabidopsis: (i) the FANCM DNA helicase and MHF1 and MHF2 co-factors 2224 , (ii) the AAA-ATPase FIDGETIN-LIKE1 25 and (iii) the RTR complex of RECQ4A, RECQ4B DNA helicases, TOPOISOMERASE3α and RMI1 2628 (Fig. 1a).…”
Section: Main Textmentioning
confidence: 99%
“…3b). This is expected due to increased class II crossovers caused by recq4a recq4b being randomly distributed 26 . However, the significant reduction in HEI10 DCO distances was unexpected, due to this gene acting in the interference-sensitive ZMM pathway 9,12 .…”
Section: Main Textmentioning
confidence: 99%